2022
DOI: 10.1002/dneu.22871
|View full text |Cite
|
Sign up to set email alerts
|

Coactivator‐associated arginine methyltransferase 1 controls oligodendrocyte differentiation in the corpus callosum during early brain development

Abstract: Protein arginine methylation has been recognized as one of key posttranslational modifications for refined protein functions, mediated by protein arginine methyltransferases (Prmts). Coactivator-associated arginine methyltransferase (Carm1, also known as Prmt4) participates in various cellular events, such as cell survival, proliferation, and differentiation through its protein arginine methylation activities. Carm1 regulates cell proliferation of a neuronal cell line and is reportedly expressed in the mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The expression of PRMT4 could be reduced in a dose‐dependent manner with the administration of TP‐064 (Figure 1e). Others have reported that PRMT 4 is expressed in the central nervous system (Ishino et al, 2022), and as PRMT4 is a type‐1 PRMT, it produces ADMA (Blanc & Richard, 2017). Our findings suggest that ADMA production is enhanced in the serum of 3xTg‐AD mice (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PRMT4 could be reduced in a dose‐dependent manner with the administration of TP‐064 (Figure 1e). Others have reported that PRMT 4 is expressed in the central nervous system (Ishino et al, 2022), and as PRMT4 is a type‐1 PRMT, it produces ADMA (Blanc & Richard, 2017). Our findings suggest that ADMA production is enhanced in the serum of 3xTg‐AD mice (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age is the single most prominent risk factor for NDDs. Although studies of OPC proliferation and differentiation in the developing nervous system have suggested a number of pathways that can be targeted to enhance remyelination in the mature nervous system (Fancy et al, 2011;Ishino et al, 2022), increasing evidence suggests that young and old OPCs are not identical (Segel et al, 2019;de la Fuente et al, 2020). In fact, a substantial loss of myelinated fibers occurs with aging (Marner et al, 2003), and remyelination is thought to be one of the major processes in the brain affected by aging (Sim et al, 2002;Neumann et al, 2019).…”
Section: Uncovering the Heterogeneity Of Oligodendroglia And The Impa...mentioning
confidence: 99%
“…Advancing age is the single most prominent risk factor for NDDs. Although studies of OPC proliferation and differentiation in the developing nervous system have suggested a number of pathways that can be targeted to enhance remyelination in the mature nervous system ( Fancy et al, 2011 ; Ishino et al, 2022 ), increasing evidence suggests that young and old OPCs are not identical ( Segel et al, 2019 ; de la Fuente et al, 2020 ). In fact, a substantial loss of myelinated fibers occurs with aging ( Marner et al, 2003 ), and remyelination is thought to be one of the major processes in the brain affected by aging ( Sim et al, 2002 ; Neumann et al, 2019 ).…”
Section: Uncovering the Heterogeneity Of Oligodendroglia And The Impa...mentioning
confidence: 99%